Interleukin polymorphisms and protein levels associated with lung cancer susceptibility and phenotypes. (2nd September 2021) - Ding, Kaiyue; Yi, Minhan; Li, Linsen; Zhang, Yuan
ABSTRACT: Background: We conducted a comprehensive analysis to explore whether multiple interleukin ( IL), IL-1β, IL-4, IL-6, IL-8 and IL-10, polymorphisms and IL proteins (IL-6, IL-10) relate to lung cancer (LC) susceptibility or clinical characteristics. Methods: We performed the standard meta-analysis procedures according to PRISMA. The odds ratio (OR) and mean difference (MD) were used for analysis. Results: We investigated 11 variants from 43 articles, and found that IL-1β rs16944 ( p = 0.04) and IL-10 rs1800872 ( p = 0.003) decreased while IL-10 rs1800896 ( p = 0.007) increased LC risks. We also found that IL-1β rs1143627 decreased NSCLC risks ( p = 0.03). The heterozygotes and homozygotes contributed differently. In addition, another 15 articles were involved to explore the relationship between IL proteins and LC. We found that LC patients accounted for higher serum IL-6 of 16.60 pg/mL ( p < 0.00001) and higher serum IL-10 of 3.47 pg/mL ( p = 0.02) than that of controls. Furthermore, IIIA-Ⅳ LC patients tended to have higher proportion of positive IL-6 staining in lung tumor tissue in contrast with IA-IIB patients by TNM stage ( p  = 0.0002). Conclusions: Four variants from IL-1β and IL-10, and serum IL-6 and IL-10 levels are associated with LC risks.